Aproximación Teórica al Concepto Integral de Logística (2019)
This article focuses on the concept of the Logistical Chain andits main functions, components and parameters. The paperillustrates the different theories and authors who assess all of thelinks of Logistical Chains and presents the theory that theUCPR research group “Marketing, Logistics and Management”has embraced.